Development of a blimp-type mobile robot platform - Olavario, Cristopher S.; Perez, Marc Milan D.; Santos, Mary Grace M. (2009.)
Aerial mobile robots can be deployed for surveillance and mapping applications above land and aquatic areas. The blimp was chosen among other aircrafts because of its ease of use, stability, safety, and silence. A commercially available, Mylar, helium-filled, RC toy blimp envelope is used as the platform. The blimp's small-scale size ensures low cost and allows it to maneuver around small spaces. The system will have proprioceptive sensors, which includes battery level sensors and a temperature sensor, along with exteroceptive sensors consisting of a digital compass, an ultrasonic sensor, and an Inertial Measurement Unit with six degrees of freedom. RF transceiver modules are used for communication between the blimp and a user terminal, which uses Python-based GUI software for output display and interactive control. Accuracy, control and stability are tested at indoor and outdoor environments. The blimp's payload objective is to support its weight along with the sensor modules.
Thesis (B.S., EEE)--University of the Philippines, Diliman.
Keywords: Mobile robots; Autonomous robots; Aerial mobile robots; Blimp-type mobile robots